(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In field conditions, the researcher collects valuable information and analyzes it to achieve his goal. During field research, the main and constant attention should be paid to the connection and relationship between the components. In particular, the interrelationship between geological structure, lithology and relief, water, climate, soil and vegetation, animal world, and economic activity of people is determined.